La planificación financiera y su efecto en la administración de los recursos económicos financieros de las micro y pequeñas empresas asociadas a la cámara de comercio y producción de la región La Libertad - año 2018. - Pollack Velásquez, Walter Mario (2018)
ABSTRACT The present investigation is referred to the study of the Financial Planning and its effect in the Administration of the Economic Resources - Financial of the Micro and Small Companies Associated to the Camera and Production of the Region The Freedom for the year 2018. The main objective is the one of determining the effects of the Financial Planning in the administration of the economic resources - financial in the MYPES associated to the CCYPLL, in the year 2018. As for the method the inductive one is applied - deductive, the population and sample is the group of associate MYPES, the techniques employees are the survey and the documental analysis and the investigation design is not experimental. The main result is shown in the obtained information of the surveys carried out the associate MYPES, as well as to the officials of the financial entities of the environment that indicate the relationship among the stadium variables, that is to say entity the Financial Planning and the Administration of the Economic Resources - Financial. The main conclusion has been this way to verify that the Financial Planning influence from a significant way to the Administration of the Resources Economic Financiers of the MYPES in study.